Komunikasi Pemasaran Politik Elite PKS Kota Bandung - muhammad sulthan (Jurnal Ilmu Komunikasi Acta Diurna, 2011)
This study aims to known what, how the elite PK-Sejahtera elite and political elite PKSejahteraconvey political messages, manage the political sense of the other party and how heknew it as a political message contained in the persuasive value. Research conducted through aninductive qualitative study of elite PK-Sejahtera, political elite PK-Sejahtera. Data obtained froman informant posing as PK-Sejahtera elites,The results showed that individual background PKS elites, political elites and the PKS regenerationand recruitment process is to determine the performance and impression managementof a politician, the way they give the impression and the sense of a political message, how to displaythe political role and how they communicate the message -political message was differentfrom other politicians. Because all informants, originating campus activists, and none of the informantsin this study had active in other parties. Thus, in managing the impression, fashion is notsomething that is very important attributes that must be optimally packaged, the most important isthe quality of the politician's "Clean and Care" Model tarbiyah conducted by elites PKS in the recruitmentsystem and system construction regeneration already a cadre of reality into reality politicsin the form of impression management. The political image of PKS who had been awakened asa party "Clean and Caring" I managed to make differentiation with other political parties. Symbolicsymbol'clean-caring' people have started asking people even believing not just clean but canclean and repair the damage. So that PKS politicians in applying Goffman Dramaturgy back statingthat the stage must be something different than the front stage, where social events and formaldisplay behavior that is not generally have to be in back stage. But it does not fully apply to PKSpoliticians either front stage or back stage in setting the political scene remains the same ie theparliamentary mission - "Clean and Caring"